J Dep Anxiety 2019
DOI: 10.35248/2167-1044.19.8.343
|View full text |Cite
|
Sign up to set email alerts
|

Yoga Improves Anxiety and Vital Signs of Women with Premenstrual Syndrome

Abstract: Objective: To study the effects of yoga on anxiety and vital signs in women that at the same time suffer from premenstrual syndrome (PMS). Material and Methods: In this randomized controlled clinical trial, yoga administered to subjects with PMS for ten weeks in three sessions with a duration of 60 minutes. Women in the control group did not do any yoga. The demographic questionnaire was filled in by subjects before the intervention. Subjects were also expressed their experiences by filling the Hamilton anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Our study found that after three months of yoga practice, participants successfully reduced the impact of premenstrual symptoms on their work, daily routine, hobbies, social activities, and relationships. These findings are consistent with previous studies [ 47 , 60 , 63 , 64 , 65 ] indicating that yoga can improve physical and mental wellness and reduce the impact of symptoms on women’s daily life.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found that after three months of yoga practice, participants successfully reduced the impact of premenstrual symptoms on their work, daily routine, hobbies, social activities, and relationships. These findings are consistent with previous studies [ 47 , 60 , 63 , 64 , 65 ] indicating that yoga can improve physical and mental wellness and reduce the impact of symptoms on women’s daily life.…”
Section: Discussionsupporting
confidence: 93%
“…Other disturbances, including feeling anxious, sensitive to rejection, and out of control, and experiencing mood swings, lowered interest, difficulty concentrating, lethargy, increased appetite, and cravings for specific foods, were significantly decreased after three months of yoga intervention. These findings are partially supported by other research [ 41 , 60 , 62 ], in which it was found that symptoms including anxiety [ 60 , 62 ], fatigue [ 60 ], reduced interest, difficulty concentrating [ 32 , 41 ], and changes in appetite [ 60 ] were improved in the yoga group.…”
Section: Discussionsupporting
confidence: 77%
“…172 Small RCTs of yoga for PMS shown positive findings on symptoms as well as dimensions such as sleep quality, but as yoga is a broad intervention compromising multiple techniques, further studies better delineating the specifics of the intervention tested are necessary. [173][174][175][176][177][178] A 2020 meta-analysis of RCTs evaluating the effect of exercise on PMS selected 15 studies of at least eight weeks duration; significant improvement in PMS symptoms was demonstrated compared to controls, but evidence quality was limited, with high heterogeneity of studies. 179 Other studies of swimming, 180 pilates, 181 traditional Chinese exercise Baduanjin, 182 and simple aerobic exercise [183][184][185] have had similar positive results, although quality of data is limited.…”
Section: Non-pharmacological Cammentioning
confidence: 99%